Association of Single Nucleotide Polymorphism -2548 G/A (rs12112075) of leptin gene with endometrial cancer and uterine leiomyomas. (November 2017) - Bieńkiewicz, Jan; Romanowicz, Hanna; Malinowski, Andrzej; Smolarz, Beata
Abstract: Aim: The aim of this study was to analyse the frequencies of genotypes and alleles of Single Nucleotide Polymorphism (SNP) -2548 G/A (rs12112075) of leptin gene ( LEP ) and an attempt to evaluate the effect this DNA marker has on endometrial cancer (EC) and uterine leiomyomas (UL). Material and methods: The study comprised 120 patients treated for endometrial cancer and 90 patients treated for uterine leiomyomas. 90 disease-free individuals were used as controls. In total, 300 patients were investigated in this research. Results: In this paper we have demonstrated that genotype AG of SNP -2548 G/A of LEP may reduce the risk of developing endometrial cancer, whereas allele A itself may be a risk factor of this malignancy. No association was found between the studied polymorphism and uterine leiomyomas. Conclusions: -2548 G/A SNP of LEP may play a significant role in the development of EC, however, uterine leiomyomas are not associated with this DNA marker.